A taxonomy of theproblem of distribution of plant processes and methods of solution - Leyva, Máximo (2013)
The plant layout problem can be generalized as a case intensively studied combinatorial optimization and therefore its nature is a NP- hard. The core of the problem originally introduced as the Systematic Distribution Planning , a multi -criteria and relatively simple, has been extended to larger contexts , through the formulation as a mathematical model based on the nature of the workshops . Given the computational complexity of the calculations have been developed heuristics ,metaheuristics and others to obtain approximate solutions . The aim of this study is to analyze recent research on plant distribution problems within the industrial context by classifying and comparing the representation of the problem , solution methods , constraints and the objective function used . The report covers more than 30 peer-reviewed articles on the subject. Particular attention is placed on recent publications that have appeared from 2008 - 2013 to focus on new developments in the State of the Art.